Modeling the Impact of Land Use Change on Basin‐scale Transfer of Fecal Indicator Bacteria: SWAT Model Performance. Issue 5 (1st September 2018) - Kim, Minjeong; Boithias, Laurie; Cho, Kyung Hwa; Sengtaheuanghoung, Oloth; Ribolzi, Olivier
Abstract : Land use change from annual crops to commercial tree plantations can modify flow and transport processes at the watershed scale, including the fate and transport of fecal indicator bacteria (FIB), such as Escherichia coli . The Soil and Water Assessment Tool (SWAT) is a useful means for integrating watershed characteristics and simulating water and contaminants. The objective of this study was to provide a comprehensive assessment of the impact of land use change on microbial transfer from soils to streams using the SWAT model. This study was conducted for the Houay Pano watershed located in northern Lao People's Democratic Republic. Under the observed weather conditions, the SWAT model predicted a decrease from 2011 to 2012 and an increase from 2012 to 2013 in surface runoff, suspended solids, and E. coli transferred from the soil surface to streams. The amount of precipitation was important in simulating surface runoff, and it subsequently affected the fate and transport of suspended solids and bacteria. In simulations of identical weather conditions and different land uses, E. coli fate and transport was more sensitive to the initial number of E. coli than to its drivers (i.e., surface runoff and suspended solids), and leaf area index was a significant factor influencing the determination of the initial number of E. coli on the soil surface. On the basis of these findings, this study identifies several limitations of the SWAT fertilizer and bacteria modules and suggests measures to improve our understanding of the impacts of land use change on FIB in tropical watersheds. Core Ideas: Watershed‐scale processes influence land use change impact on FIB transport. The amount of precipitation significantly influences bacteria transport. FIB transport is sensitive to FIB number on soil surface, itself determined by LAI. We report several limitations of the SWAT model when describing FIB transfer. We suggest model improvements to understand the impact of land use change on FIB.